THE DEVELOPMENT OF AN ENGLISH TEACHING LESSON PLAN BASED ON MARRIOTT STANDARDS FOR THE FRONT OFFICE DEPARTMENT AT SMA KARYA WISATA - Dewi, Komang Manik Listia; Juniarta, Putu Adi Krisna; Wahyuni, Luh Gede Eka (PEMA, 2025)
This study developed an English teaching lesson plan based on Marriott Standards for eleventh grade students at SMA Karya Wisata Penarukan. The research addressed the gap between general English materials and the communicative needs of the hospitality industry, using an English for Specific Purposes (ESP) approach integrated with authentic Front Office SOPs from Marriott. The research adopted the Design and Development model by Richey and Klein (2007) through analysis, design, development, and evaluation stages. Needs analysis was conducted through classroom observations, document analysis, and teacher inteviews to identify students needs and learning challenges. The ESP-based lesson plan was then designed covering key Front Office topics such as Reservations, Check-in and Check-out, guest complaint handling using the LEARN model, and courtesy calls. The lesson plan was validate by two experts in ESP and Hospitality education using an expert validation rubric. The results showed an average score of 4.55 (excellent), demonstrating high relevance, language appropriatness, instructional quality, practicality, and alignment with Marriott Standards. The findings indicate that the developed lesson plan is feasible and effective in supporting English learning and improving students professional communication skills in Front Office contexts.